Prática fonoaudiológica com pacientes disfágicos em contexto hospitalar: aspectos biopsiquicos - Duarte, Maria José de Freitas (2006)
This essay discusses the organic psichical and social aspects present in dysphagia cases which influence positively or negatively the therapeutic speech language process applied in a hospital environment Initially a bibliographic revision of organic aspects of dysphagia with a characterization of its symptoms and etiology was conduted as forms of treatment and procedure used in the rehabilitation of functional and oral dysphagic patients However these aspects are not sufficient to explane the main survey of this dissertation Why sme patients capable of initiating a normal oral diet cannot comply or even resist in doing it Based on aspects of psychoanalytic and phonoaudiologic theories it was perceived angush fear uncertainties interfering in process of cure By means of study of two clinical cases it concluded that the phono therapist can articulate the organic and psycological dimensions in the treatment of dysphagic patients devising a therapy that involves both perpectives This means that the therapist and team responsible for such cases must reach teoretical means to develop and differentiate clinical approaches aware of the questions and personal sufferings broght by the patients turning them into active participants of the therapeutic process of care and by this way humaning the attendance Concluding therefore that it is possible to treat a dysphagic patient and not only dysphagia also in the hospital environment